PLAYING SOMETHING SERIOUS: TRADITIONAL GAMES IN THE CONTEXT OF SCHOOL PHYSICAL EDUCATION CLASSES (Fiep Bulletin - online, 2016)
Despite the great technological development and the processes of globalization that permeates the modern society, childhood has also been transformed through the social advances and various demands as: violence, the lack of free spaces, excess electronic toys between other. As regards the school and childhood, the traditional games are not present in schoolyards and the school there is much do not seek to enhance the traditional ludic culture.In this way, the objective is to investigate, through ludic memory, the traditional games of authors social (parents and students) and its importance as a pedagogical instrument during physical education classes.In this context, comes the questioning: as the traditional games can contributes to the promotion of cultural memory in the context of Physical Education classes?or both, we seek to discuss the importance of the traditional games and play as valorization of cultural memory and check the incorporation of traditional games and play during physical education classes.This study if configures an action research where it was possible: to observe, analyze, interpret and act implementing actions in the environment searched. Using as a basis the bibliographical authors as Fantin(2000); Rangel-Betti(2001);Catunda (2005) Moyles(2006), Bacelar de (2012) among others as theoretical support. In addition to the interview and intervention, using as sample population students from the 1st year of Basic Education, between 6 to 7 years old and their parents/ responsible. The traditional games and activities are part of the cultural patrimony playground through games, toys, songs and stories transmitted from generation to generation.And lose their characteristics in function: the lack of adequate and safe spaces for contact with groups of children of their community; by technological variety of toys that hinder the classroom interaction with the other to share discoveries, victories and defeats in addition to the lack of time and contact family to share attitudes, GESTURES, EXPERIENCES AND EMOTIONS OF THE PLAYS THAT HAVE MARKED THE LUDIC CHILDHOOD FAMILY.
Keywords: Traditional joke. The ludic culture; Physical Education